2012
DOI: 10.2147/bctt.s32766
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic reduction mammoplasty in large-breasted women with cancer using superior and superomedial pedicles

Abstract: Therapeutic reduction mammoplasty using superior and superomedial pedicles was shown to be oncologically safer than traditional conservative surgery. This oncoplastic procedure yields a satisfactory esthetic outcome with lower morbidity in large-breasted women with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…We believe that this favorable outcome is in part due to the anatomical arrangement of the vascular pedicle that lies away from the tumor bed, which minimized the conflict between oncological and reconstructive intraoperative decisions and allowed an effective oncoplastic procedure. In our study, the esthetic outcome was found to be higher than in other studies (73.3% patients were scored as excellent versus 64% by Denewer et al 23 ).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…We believe that this favorable outcome is in part due to the anatomical arrangement of the vascular pedicle that lies away from the tumor bed, which minimized the conflict between oncological and reconstructive intraoperative decisions and allowed an effective oncoplastic procedure. In our study, the esthetic outcome was found to be higher than in other studies (73.3% patients were scored as excellent versus 64% by Denewer et al 23 ).…”
Section: Discussioncontrasting
confidence: 85%
“…Our complications rate is probably better than that with other techniques that use the superomedial pedicle or the inferior pedicle. 22 In a study by Denewer et al, 23 which used a superomedial pedicle, the rate of wound dehiscence was 8% (four out of 50 cases) and the rate of partial necrosis of the areola was 4% (two out of 50 cases). A study by Gulcelik et al 24 using the inferior pedicle reported an incidence of 3% minor wound dehiscence, 1% major wound dehiscence, 1% areolar necrosis, and 5% seroma.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recurrence rate in our study was also comparable with similar studies such as 3% in Rietjens et al' study 18 19,23,24,26,27 Oncologic treatments have an undeniable role in the success of breast cancer treatment (presurgically making the tumor operable and postsurgically eliminating the residual disease); however, it is the achievement of ''clear surgical margins'' that has a significant impact on the 10-year diseasefree survival and also is the most important factor to reduce the risk for local recurrence. 28 Based on this, rather than counting on the efficacy of oncologic treatments, the focus of the treatment should primarily be on obtaining free surgical margins by precise resections at the first oncologic operation.…”
Section: Commentssupporting
confidence: 92%
“…However, RM presents the risk of several specific complications which are not commonly encountered in tumorectomy, such as tissue necrosis, with the main perpetrator being necrosis of the nipple‐areolar complex . Such complications are reported to occur at an incidence ranging from 0.6% to 4% (2.3% in our experience), and their appearance does not lead to a delay in the initiation of adjuvant treatments when compared to tumorectomy . Importantly, the incidence of postoperative complications appears to decrease if RM is performed immediately.…”
Section: Discussionmentioning
confidence: 74%